Personalized Medicines: Reforming Diagnostics and Therapeutics - Poonam Yadav ,; Sheefali Mahant, (Journal of Basic & Applied Sciences, 2015)
Since the first use of the term ‘Personalized Medicine’ (PM) in 1990, many research and review articles have coined this term. Nevertheless, this topic has not been widely researched about till now. The PMs are the application of genomic and molecular data for developing therapies with unprecedentedly higher efficiencies, better safety, lower ADR’s, and reduced costs of therapies. PMs are developed through molecular level knowledge of the drug targets and diseases, which leads to the promise of the right treatment for right patient at the right time. This paper gives a comprehensive view of PMs. For this purpose, this paper is divided into following sections: defining personalized medicines; the history and evolution of personalized medicines; the human genome project; drug discovery & development process; merits of personalized medicines; applications of personalized medicines; challenges on the road of personalized medicines; regulatory evolution in the generation of personalized medicines; role of US FDA in the era of personalized medicines and, conclusion.